Genetic trends in weights and weight gains of "Guzerá" cattle - de Oliveira, João Ademir; Lôbo, Raysildo Barbosa; de Oliveira, Henrique Nunes (Pesquisa Agropecuaria Brasileira, 1995)
The main objective of this study was to estimate genetic and phenotypic trends in weights at birth (BW), 8 (W8) and 12 months (W12) of age; and also in the daily gains from birth to 8 months (G8) and from birth to 12 months (G12) for the "Guzerá" cattle herd from the "Fazenda de Ensino e Pesquisa do Campus de Ilha Solteira", UNESP, at Selvíria, MS, in the Central-West region of Brazil. The data were collected between 1979 and 1984 from 842 calves, sired by 22 sires. Genetic trends were estimated by three alternative procedures, two of them were based on the methodology of repeated use of sires and the other procedure on the difIerences in the average genetic values of sires in the different years. The phenotypic annual changes estimated were -0.232 kg, -8.278 kg, -0.033 kg, -8.498 kg e -0.023 kg, for BW, W8, G8, W12 and G12, respectively. The estimates of genetic trends, obtained by the three procedures were different, but showed that genetic changes for all analised traits were little.